Global, regional, and national burden of ovarian cancer in women aged 45 + from 1990 to 2021 and projections for 2050: a systematic analysis based on the 2021 global burden of disease study - Yanan Ren; Ren Xu; Yazhuo Wang; LuYang Su; Jianzhi Su (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Ovarian cancer is the most common cause of gynecologic cancer-related deaths. We aimed to assess the global, regional, and national burdens and trends of Ovarian Cancer in Women Aged 45 + from 1990 to 2019 and Projections for 2050, utilizing data from the most recent Global Burden of Disease (GBD) 2021 database. Methods Age-standardized rates of incidence, prevalence, mortality, and disability-adjusted life years (DALYs) were analyzed using GBD 2021 data. Temporal trends were assessed using estimated annual percentage change (EAPC). Regional disparities were examined via the Socio-Demographic Index (SDI). Age-Period-Cohort (APC) models assessed disease dynamics, while Bayesian APC (BAPC) modeling projected trends to 2050. Results In 2021, global ovarian cancer incidence, prevalence, mortality, and DALYs in women aged 45 + were 239,682; 843,405; 171,246; and 4,352,539, respectively. The global burden declined significantly from 1990 to 2021 and is projected to remain stable through 2050. However, regional disparities persist: High and High-middle SDI regions saw decreases, while Middle to Low SDI regions experienced increases. Burden increased with SDI up to 0.8, then declined. Population growth was the primary contributor, followed by epidemiologic transitions and aging. The 55–59 age group showed the highest morbidity and DALYs; mortality peaked at 65–69 years. Conclusions Although the overall burden of ovarian cancer in women aged 45 + is declining globally, marked regional disparities underscore the need for tailored prevention and treatment strategies to further reduce disease impact and improve outcomes.